Mathematical modeling and numerical analysis of nonstationary plane-parallel flows of viscous incompressible fluid by r-functions and galerkin method - Artyukh, A.; Sidorov, M. (LUBLIN–RZESZOW, 2014)
This paper is dedicated to nonstationary plane-parallel flows of viscous incompressible fluid in finite simply connected domains. Theorem of the solution uniqueness is presented. The method of successive approximation, the Galerkin method and the R-functions method are used to obtain the numerical solution, which was tested on the problem with known solution
Keywords: nonstationary flow; incompressible fluid; stream function; method of successive approximation